AB0195 HEME oxygenase-1 expression is decreased in monocytes from patients with systemic lupus erythematosus. (23rd January 2014) - Llanos, C.; Mackern, J.; Herrada, A.; Carreño, L.; Gomez, R.; Anegon, I.; Iacobelli, S.; Kalergis, A.
Abstract : Background: Systemic Lupus Erythematosus (SLE) is a chronic autoimmune disease characterized by alterations affecting both the innate and adaptive immune systems [1]. Monocytes and dendritic cells from SLE patients display a stimulatory phenotype that promotes the activation of self-reactive T cells [2]. Monocytes are pluripotent cells capable of engulfing pathogens, releasing inflammatory molecules and presenting antigens to naïve T cells. One of the key molecules that controls monocyte function is Heme oxigenase-1 (HO-1), which catalyzes the degradation of heme into biliverdin, carbon monoxide (CO) and Fe+2. CO possesses immunosuppressive and anti-inflammatory abilities [3]. Objectives: Therefore, the goal of this work was to assess HO-1 expression in monocytes from SLE patients and healthy controls (HC). Methods: 43 non-selected SLE patients that fulfilled the ACR criteria for SLE and 30 HC were recruited. In addition, 5 kidney-transplanted patients undergoing similar immunosuppressive treatment were included. All patients signed an informed consent form before entering the study. PBMCs were separated using the standard Ficoll centrifugation method. CD14+ monocytes and CD4+ T cells were sorted by FACS and HO-1 expression was measured by RT-PCR. HO-1 protein expression was determined by FACS. T cell activation parameters after staphylococcal enterotoxin A (SEA 50nM) stimulation were determined by FACS (IL2; CD69; CD25). Results: HO-1 mRNA levels were significantly decreased in CD14+ monocytes from SLE patients compared to HC (P<0.0075, Unpaired t test). When HO-1 protein expression in monocytes was assessed, similar results were observed (HO-1 relative expression (Geo mean SLE patient/Geo mean HC]; 0.73±0.05, P<0.0001 (Unpaired t test)). No differences in HO-1 mRNA levels or protein expression were observed between CD4+ T cells from SLE patients and HC. No differences between transplanted and lupus patients were found when HO-1 monocyte transcripts were evaluated in monocytes and CD4 + T cells. To assess the immunogenic capacity of monocytes, T cell activation assays in response to SEA stimulation were performed. No significant differences in T cell activation parameters, such as IL-2 production and CD69 expression were observed between lupus patients and HC. Conclusions: We found a significant decrease in HO-1 expression in monocytes from SLE patients, suggesting that an imbalance in HO-1 could play a role in SLE pathogenesis. The results obtained in kidney-transplanted patients suggest that this observation is not due to the immunosuppressive treatment. Since the results observed in SEA activation assays could be explained by defects in T cells from SLE patients, additional experiments to further evaluate the role of HO-1 in monocytes function are warranted. References: Llanos, C., et al. Curr Gene Ther 2011; 11(6). Steinbach, F., et al. Ann Rheum Dis 2000; 59(4): p. 283-8. Remy, S., et al., J immunol 2009; 182(4): p. 1877-84. Disclosure of Interest: None Declared